SARS-CoV-2-Related Pediatric Encephalopathy with Biphasic Convulsions and Cortical Blindness: A Case Report - Shiraishi, Yuriko; Tomari, Kouki; Matsuoka, Tsuyoshi; Numazawa, Masaya; Matsuoka, Takashi (Journal of Pediatric Neurology, 2023)
Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is an encephalopathy syndrome that develops during the febrile phase of infection and is characterized by biphasic seizures and bright tree appearance (BTA) on imaging. In this study, we examined a 1-year-old child who was diagnosed with AESD caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. He had a fever for 2 days and was diagnosed with coronavirus disease 2019 on the day of consultation based on a positive antigen test for SARS-CoV-2. The seizures had stopped on arrival to hospital; however, symptoms of encephalopathy persisted. Despite being treated for acute encephalopathy with steroid pulse therapy, vitamins, and remdesivir, he had poor expressive language, and electroencephalography showed generalized slow waves. A repeat head magnetic resonance imaging showed BTA in the parietal and occipital lobes, and seizures recurred during hospital stay. He was also found to have cortical blindness. At the 4-month follow-up, the vision gradually improved and the hand movements recovered. SARS-CoV-2 infection can cause febrile convulsions, which can lead to the development of AESD. Furthermore, a subtype of AESD has occipital lobe predominant lesions that can cause visual impairment.
Keywords: acute encephalopathy; biphasic seizures; reduced diffusion; bright tree appearance